The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3897/zoologia.35.e14641
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance of the zoea I stage of four Neotropical crab species (Crustacea: Decapoda)

Abstract: . Although larval stages are often considered particularly vulnerable to stressors, for many marine invertebrates studies of thermal tolerance have focused on adults. Here we determined the upper thermal limit (LT50) of the zoea I of four Caribbean crab species (Macrocoelomatrispinosum, Aratuspisonii, Armasesricordi, and Minucarapax) and compared their thermal tolerance over time and among species. The zoea from the subtidal species M.trispinosum and tree climbing mangrove species A.pisonii had a lower thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Comparisons of closely related species that occur proximal to each other but in differing thermal environments (e.g. different tide heights) including barnacles, gastropods and crabs show that thermal tolerance of embryos and larvae reflects the temperature regime of the adult microhabitat and this is likely to influence dispersal (Morley et al, 2017; Rebolledo & Collin, 2018). There do not, however, appear to be any studies of larval offspring thermal tolerance for species that co‐occur in the same habitat and temperature environment, as we do here for two sea urchin species.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of closely related species that occur proximal to each other but in differing thermal environments (e.g. different tide heights) including barnacles, gastropods and crabs show that thermal tolerance of embryos and larvae reflects the temperature regime of the adult microhabitat and this is likely to influence dispersal (Morley et al, 2017; Rebolledo & Collin, 2018). There do not, however, appear to be any studies of larval offspring thermal tolerance for species that co‐occur in the same habitat and temperature environment, as we do here for two sea urchin species.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, our findings showed that long-term exposure at various water temperature treatments can be used to determine the optimal water temperature, similar to how short exposure treatment can be used to determine preferred temperature. Chronic exposure to thermal stress allows determination of its effects on larval growth and survival [ 55 ], and on the levels of tolerance, behavior, and physiological effects [ 56 ]. Study of both chronic and acute thermal tolerance of intertidal biota is still lacking [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…tranquebarica from tropical region which temperature below than 26℃ was considered low and unsuitable for embryo development. The ability for egg acclimation according to the temperature encountered in their natural habitat (Rebolledo & Collin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…tranquebarica (Baylon, 2013). Despite these larvae from a similar genus, the optimal temperature was distinct due to the ability for larval acclimation according to the temperature encountered in the natural habitat (Rebolledo & Collin, 2018). This phenomenon was also proven by Meynecke et al (2010) which reviewed the temperature adaptation of larval mud crab from similar species, found the optimal range for Japanese S .…”
Section: Discussionmentioning
confidence: 99%